Larval development of Boccardia knoxi , a shell‐infesting spionid polychaete - Sean J. Handley (New Zealand Journal of Marine and Freshwater Research, 2000)
Larvae of Boccardia knoxi (Rainer) were reared in the laboratory after dissection from brood capsules extracted from the outer shell and perio‐stracum of Cookia sulcata and Haliotis iris collected from Tasman Bay, New Zealand. All the eggs within each brood capsule developed into embryos. The dissected larvae had provisional setae and fed on phytoplankton. Larval development is described through to metamorphosis.